Speckle tracking echocardiographic analysis of left ventricular systolic and diastolic function in young elite rugby players - Mandigout, S.; Maufrais, C.; Cornette, T.; Alaphilippe, A.; Daviet, J. C. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Little evidence exists in the literature on the effects of mixed-type training on the left ventricle (LV). This study focused on the effects of training on the morphological and functional characteristics of the left ventricle. This study investigated the effects of training on LV function using Speckle Tracking Imaging (STI) in high-level, young rugby players.